MacWilliams identity for m-spotty Lee weight enumerators - Siap, Irfan (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
It is a well established fact that m-spotty byte error control codes provide a good source for detecting and correcting errors in semiconductor memory systems using high-density RAM chips with wide I/O data (e.g. 8, 16 or 32 bits). Recently, a MacWilliams identity that establishes an important relation between an m-spotty weight enumerator of a binary code and its dual has been proven in Kazuyoshi Suzuki et al. (2007) 15). In this paper, we introduce the m-spotty Lee weights and the m-spotty Lee weight enumerator of a quaternary code and prove a MacWilliams type identity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Quaternary codes; MacWilliams identity; m-spotty weights; Lee weight enumerator; CODES; Mathematics